PENGARUH LIKUIDITAS DAN RENTABILITAS TERHADAP RASIO KECUKUPAN MODAL PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mike Kusuma Dewi; Nadia Rapika Dewi (LPPM Universitas Bina Bangsa, 2022)
The capital adequacy ratio is an aspect that predicts whether the funds owned by a bank are sufficient to support its operational activities. In other terms, the bank can repay the disbursement of the depositor’s fees within the time it is billed and can fulfill the credit request that has been submitted. The purpose of this study is to determine the effect of liqiudity on the capital adequacy ratio and the effect of profitability on the capital adequacy ratio of banking companies listed on the indonesian stock exchange in 2018-2020. The method used in this study is quantitative. The type of data used is panel data. Panel is a combination of time series data with cross section data. Sources of data in this study using secondary data. The population in this study are all banking companies listed on the indonesia stock exchange in 2018-2020 totalling 44 companies. The sampling technique was using purposive sampling technique. The analysis technique in this research is panel data regression.Based on the results of the study, all independent variables have a simultaneous effect on the capital adequacy ratio. Partially, liquidity has a significant effect on the capital adequacy ratio and profitability has a significant effect on the capital adequacy ratio